Enhanced Stokes Shift and Phase Stability by Cosynthesizing Perovskite Nanoparticles (MAPbI3/MAPbBr3) in a Single Solution. Issue 11 (7th July 2022) - Munir, Muhammad; Tan, Jinglan; Arbi, Ramis; Oliveira, Pedro; Leeb, Elisabeth; Salinas, Yolanda; Scharber, Markus Clark; Sariciftci, Niyazi Serdar; Turak, Ayse
Abstract : Herein, diblock copolymer reverse micelle templating (RMD) is used to control the reaction kinetics of metal halide hybrid perovskites formation to fabricate systems showing dual‐phase emission. Through micelle templating, desired compositions can be engineered which show high phase stability of mixtures of perovskite nanoparticles (NPs) through micellar shielding and stabilizing of the cage structure. In addition, Stokes shift of around 150 nm, one of the largest reported for perovskite systems, can be obtained with careful control over synthesis kinetics. Using an unconventional approach, that is, mixing methylammonium iodide (MAI) and lead bromide PbBr2, systems consisting of both green‐ and red‐emitting NPs are fabricated by a two‐step reaction process using RMD. By obtaining two stable phases in a single solution, the NP system can absorb in the ultraviolet region and emit in the red region, making them excellent candidates for downconversion to improve solar cells efficiency, as shown for two polymer active layers in organic bulk heretojunction solar cells (OPVs). Exploiting the phase stabilizing effect of the micelles, the reaction kinetics of perovskite formation can be tuned for various halide substitutions, opening up new avenues for coexisting perovskite phases for photovoltaic and light‐emitting applications. Abstract : Taking advantage of slower reaction kinetics using diblock copolymer reverse micelle templates, dual‐emission organohalide perovskite nanoparticles with large Stokes shift can be used as UV downconverters for absorbance‐matched organic photovoltaics.